THE PRINCIPLES OF COMMERCIAL BANK LENDING - السيد غباشی د.محمد (Dirasat in Economics and Business, 1966)
The article deals in its introductory part with the definition and scope of business of the commercial bank. The commercial bank is defined to be a financial institution which receives short term funds and offers them in the form of short term credits. The nature of the funds held at the disposal of a financial institution determines the nature of its assets. While the financial resources of the commercial bank consist largely of call and short notice deposits and thus allow short term credit facilities, the financial resources held at the disposal of the long term credit institutions such as Industrial and Agricultural Banks consist of bonds and long term capital donations and thus allow long term advances to clients. Although the traditional view in commercial banking oractice allows no long term advances, the German commercial banking practice does not seem to apply this "golden rule" strictly. German commercial banks known as "Kreditbanken" sometimes engage their funds in long term investments. This is usually true of the promotion and definite taking over of new canital issues. The advances of a commercial bank are always known to be selfliquidating, i.e., as Professor Sayers says, "a loan which the debtor is thought to be able to repay because there is evidence (often in the shape of shipping documents or warehouse receipts held by one of the parties) that he is engaged in a genuine commercial operation closure of which will provide him with the withdrawal for payment". They are thus * Dr. Ghobashy graduated from the Faculty of Commerce, Alexandria University in June 1954 and followed higher studies at the same Facultv till 1960. In 1963 he obtained the Doctor's degree from the Hochshule fuer Welthandel, Vienna Austria. He has had 15 years bank practice, including training in England and West Germany. During his career he has been in charge of the International Control Dept. and then Technical Advisor.